Introduction of Basic Mathematics Through Traditional Dakon Games in Children Aged 4-5 Years: A Qualitative Study at Pertiwi Ngiyono Kindergarten - Putri, Adistya Amelia Nirmala; Fauziyah, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this study is to examine the effectiveness of dakon games in increasing children’s enthusiasm and engagement in learning basic mathematical skills through enjoyable play-based activities. Methodology: This research adopts a qualitative methodology to explore how teachers and students perceive and experience the learning process using dakon games. Data were collected through classroom observations and teacher interviews. Results: The findings are expected to reveal the benefits of introducing fundamental mathematical concepts through dakon, showing how traditional games can support learning motivation and participation. Applications/Originality/Value: This study highlights the importance of integrating local cultural elements—such as the traditional dakon game—into the educational process. It offers a culturally responsive approach to teaching mathematics, promoting both engagement and cultural preservation in early education.